An orthogonal experimental study on the effect of temperature shock parameters on methane adsorption and desorption properties of mudstone - Yawei ZHENG; Jianting KANG; Tianhe KANG; Jiaxin YAN; Jiachang WANG; Huihui ZHANG (Meikuang Anquan, 2024)
In order to investigate the effect of temperature shock action parameters on the methane adsorption and desorption of mudstone, a temperature shock modification test was conducted on the mudstone in the roof of 15303 working face of 15# coal seam in Sihe Coal Mine using orthogonal test method. The 3 factors and 4 levels were hot shock temperature of 50, 100, 150 and 200 ℃, cold shock temperature of −10, −30, −50 and −70 ℃, and the number of shock cycles of 1, 3, 5 and 7. The volumetric method was used to determine the characteristic parameters of adsorption and desorption of mudstone under different action parameters and to investigate the influence mechanism in terms of pore structure. The results showed that the mudstone methane adsorption and desorption capacity increased after modification with different action parameters, and the effects on the saturation adsorption capacity, Langmuir pressure, specific surface area and most probable pore size were in the following order: heat shock temperature > number of cycles > cold shock temperature; the effects on the desorption rate, diffusion coefficient and pore volume were in the following order: number of cycles > cold shock temperature > heat shock temperature. The saturation adsorption capacity increased the most at the heat shock temperature of 200 ℃, the cold shock temperature of −50 ℃ and the number of shock cycles of 3 times, 23.29%, 15.60% and 19.15% respectively; the final desorption rate increased the most at the heat shock temperature of 150 ℃, the cold shock temperature of −70 ℃ and the number of shock cycles of 5 times, 7.15%, 11.54% and 11.14% respectively. In terms of pore structure, the saturated adsorption capacity of the mudstone has a good linear relationship with the specific surface area and the most available pore size, and the desorption rate has a good linear relationship with the pore capacity, while the specific surface area and pore volume of the modified mudstone are increased and the most probable pore size is reduced resulting in increased methane adsorption and desorption capacity of the mudstone. In terms of surface properties, the modification reduces the surface roughness, increases the mudstone-water contact angle and reduces the surface energy.